The Effectiveness Of Using Artificial Intelligence (AI) Technology In Enhancing Junior High School Students’ Mathematical Problem Solving Skills - Siregar, Febry Azmiana; Silalahi, Niken Adelina; Barus, Emya Lavigana; Armelia Rosi, Feby; Christin Sitanggang, Cornelia Valent; Sihombing, Hanna Novita; Sitohang, Daniel (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This study aims to evaluate the effectiveness of using Artificial Intelligence (AI) technology through ChatGPT in enhancing junior high school students’ mathematical problem-solving skills. The research employed a quantitative method with a quasi-experimental design, specifically the pretest-posttest control group design, involving two groups: an experimental class using ChatGPT and a control class using conventional learning methods. The study involved 52 eighth-grade students at SMP Adhyaksa Medan, selected through purposive sampling. The research instruments included pretest and posttest assessments to measure problem-solving skills. Data analysis showed a significant improvement in both groups, with the experimental group showing a higher increase. The independent t-test revealed a significant difference between the posttest results of the two groups, and the N-Gain calculation showed an average of 69.85 in the experimental group (medium category) and 29.85 in the control group (low category). These findings indicate that using ChatGPT as an AI-based interactive learning tool is effective in improving students’ mathematical problem-solving skills.